Dispersal capacity of Haematopota spp. and Stomoxys calcitrans using a mark–release–recapture approach in Belgium. Issue 3 (18th January 2018) - Lempereur, L.; Sohier, C.; Smeets, F.; Maréchal, F.; Berkvens, D.; Madder, M.; Francis, F.; Losson, B.
Abstract: The dispersion potential of mechanical vectors is an important factor in the dissemination of pathogens. A mark–release–recapture experiment was implemented using two groups (unfed and partially fed) of the Tabanidae (Diptera) ( Haematopota spp.) and biting Muscidae (Diptera) ( Stomoxys calcitrans ) most frequently collected in Belgium in order to evaluate their dispersion potential. In total, 2104 specimens of Haematopota spp. were collected directly from horses and 5396 S. calcitrans were collected in a cattle farm using hand‐nets. Some of these insects were partially fed in vitro and all were subsequently coloured. Overall, 67 specimens of S. calcitrans (1.2%) and 17 of Haematopota spp. (0.8%) were recaptured directly on horses. Stomoxys calcitrans flew maximum distances of 150 m and 300 m when partially fed and unfed, respectively. Haematopota spp. travelled maximum distances of 100 m and 200 m when partially fed and unfed, respectively. Segregation measures seem essential in order to reduce the risk for pathogen transmission. A distance of 150 m appears to be the minimum required for segregation to avoid the risk for mechanical transmission, but in areas of higher vector density, this should probably be increased. Abstract : The dispersion potential of mechanical vectors is an important factor in the dissemination of pathogens. A mark–release–recapture experiment was implemented using unfed and partially fed Tabanidae (2104 Haematopota spp.) and biting Muscidae (5396 Stomoxys calcitrans ) in Belgium. A segregation distance of 150 m appears to be the minimum required to avoid mechanical transmission, but in areas of higher vector density, this should probably be increased.